Fast and frugal trees: translating population-based pharmacogenomics to medication prioritization. (March 2015) - Rooij, Tibor van; Roederer, Mary; Wareham, Todd; Rooij, Iris van; McLeod, Howard L; Marsh, Sharon
Aim: Fast and frugal decision trees (FFTs) can simplify clinical decision making by providing a heuristic approach to contextual guidance. We wanted to use FFTs for pharmacogenomic knowledge translation at point-of-care.Materials & Methods: The Pharmacogenomics for Every Nation Initiative (PGENI), an international nonprofit organization, collects data on regional polymorphisms as a predictor of metabolism for individual drugs and dosages. We advanced FFTs to work with PGENI pharmacogenomic data to produce medication recommendations that are accurate, transparent and straightforward to automate.Results: By streamlining medication selection processes in the PGENI workflow, information technology applications can now be deployed.Conclusion: We developed a decision tree approach that can translate pharmacogenomic data to provide up-to-date recommended care for populations based on their medication-specific markers.